2012
DOI: 10.1093/mp/ssr113
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the Arabidopsis thaliana Jasmonic Acid/Ethylene-Induced Defense Pathway by TGA-Interacting Glutaredoxins Depends on Their C-Terminal ALWL Motif

Abstract: Glutaredoxins are small heat-stable oxidoreductases that transfer electrons from glutathione (GSH) to oxidized cysteine residues, thereby contributing to protein integrity and regulation. In Arabidopsis thaliana, floral glutaredoxins ROXY1 and ROXY2 and pathogen-induced ROXY19/GRX480 interact with bZIP transcription factors of the TGACG (TGA) motif-binding family. ROXY1, ROXY2, and TGA factors PERIANTHIA, TGA9, and TGA10 play essential roles in floral development. In contrast, ectopically expressed ROXY19/GRX4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
204
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(227 citation statements)
references
References 31 publications
5
204
0
9
Order By: Relevance
“…Our map-based cloning revealed that Abph2 encodes a GRX gene. Plant GRXs function in defense against various stresses, hormone signaling, and flower development (Ndamukong et al, 2007;Cheng, 2008;Xing and Zachgo, 2008;Guo et al, 2010;Cheng et al, 2011;Zander et al, 2012). Remarkably, we found that Abph2 arose by a transposition of MSCA1, and this rearrangement was presumably caused by the ionizing radiation that induced the Abph2 mutation.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our map-based cloning revealed that Abph2 encodes a GRX gene. Plant GRXs function in defense against various stresses, hormone signaling, and flower development (Ndamukong et al, 2007;Cheng, 2008;Xing and Zachgo, 2008;Guo et al, 2010;Cheng et al, 2011;Zander et al, 2012). Remarkably, we found that Abph2 arose by a transposition of MSCA1, and this rearrangement was presumably caused by the ionizing radiation that induced the Abph2 mutation.…”
Section: Discussionmentioning
confidence: 61%
“…Based on the conserved active site sequences, plant GRXs are divided into CPYC-, CGFC-, and CC-type classes. Plant GRX genes function in stress and pathogen responses (Ndamukong et al, 2007;Cheng, 2008;Guo et al, 2010) as well as jasmonic acid, gibberellic acid, and auxin signaling (Hou et al, 2008;Cheng et al, 2011;Zander et al, 2012). In Arabidopsis, two related CC-type GRX genes, ROXY1 and 2, were found to function in flower development (Xing et al, 2005(Xing et al, , 2006Xing and Zachgo, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the GCC-box is sufficient for transcriptional activation by JA and suppression by SA and suggest that SA/JA crosstalk via the GCC-box is mediated through SA-mediated suppression of ORA59 protein accumulation. Like PDF1.2, the promoter of ORA59 contains a GCC-box and can be suppressed by SA (Zander et al, 2012). However, we showed that this is not required for SA-mediated suppression of JA-dependent PDF1.2 gene expression, as in the ERF1 overexpression line the level of ORA59 transcript is not affected by SA while the at same time the PDF1.2 expression level is reduced by SA ( Figure 6A).…”
Section: Mode Of Action Of Sa/ja Signal Interactionmentioning
confidence: 79%
“…5 Unique Peptides displays the number of peptide sequences unique to a protein group. 6 Peptides displays the number of distinct peptide sequences in the protein group. 7 PSM displays the total number of identified peptide sequences (PSMs) for the protein, including those redundantly identified.…”
Section: Immunoblotting Protein Detection and Tryptic Digestionmentioning
confidence: 99%
“…3,4 TGA factors belong to the basic region/leucine zipper motif (bZIP) superfamily of transcription factors; 5 they bind to tfhe TGACG motif to regulate defense and developmental processes. 6,7 Different methods have been used to study interactions between TGA factors and other proteins. Y2H screens were used to show that 7 TGA factors differentially interact with a key regulator of systemic acquired resistance (SAR), NPR1.…”
Section: Introductionmentioning
confidence: 99%